ANALISIS DAYA SAING USAHA TANI KAKAO DI KABUPATEN PESAWARAN - Puspitasari, Nindi Galuh; Abidin, Zainal; Kasymir, Eka (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
Lampung Province is the sixth largest national cocoa producer. However, the volume of cocoa production produced over the last 5 years, 2018-2022, shows a downward trend. The average cocoa production in Lampung Province in the 2018-2022 period was 50% produced by Pesawaran District. The competitiveness of cocoa farming in Pesawaran District will be affected by the decline in production. This study is to analyze the competitive and comparative advantages, and the effects of fertilizer subsidy and export tax policy on cocoa farming in Pesawaran District. The research was conducted in Gedong Tataan Subdistrict, Pesawaran District, which was chosen purposively. The respondent obtained a sample of 54 farmers who were determined using the simple random sampling method. Data analyzed using the Policy Analysis Matrix (PAM) method. The results showed that cocoa farming in Pesawaran District has a competitive advantage as indicated by a PCR value of 0.55 and a comparative advantage with a DRCR value of 0.44. The fertilizer subsidy policy provides benefits to cocoa farmers because it causes lower input prices by 45% (NPCI 0.55), while the export tax policy does not provide benefits to farmers because it causes farmer's private revenue to be lower than social because the private price of cocoa is lower by 78% than the social price (NPCO 0.78).